Ultrahigh-pressure metamorphism and exhumation of garnet-bearing ultramafic rocks from the Lanterman Range (northern Victoria Land, Antarctica) - Palmeri, R. (R.); Ghiribelli, B. (B.); Ranalli, G. (Giorgio); Talarico, F. (F.); Ricci, C.A. (C. A.) (Journal of Metamorphic Geology, 2007)
Northern Victoria Land is a key area for the Ross Orogen - a Palaeozoic foldbelt formed at the palaeo-Pacific margin of Gondwana. A narrow and discontinuous high- to ultrahigh-pressure (UHP) belt, consisting of mafic and ultramafic rocks (including garnet-bearing types) within a metasedimentary sequence of gneisses and quartzites, is exposed at the Lanterman Range (northern Victoria Land). Garnet-bearing ultramafic rocks evolved through at least six metamorphic stages. Stage 1 is defined by medium-grained garnet+olivine+low-Al orthopyroxene+clinopyroxene, whereas finer-grained garnet+olivine+orthopyroxene+clinopyroxene+amphibole constitutes the stage 2 assemblage. Stage 3 is defined by kelyphites of orthopyroxene+clinopyroxene+spinel±amphibole around garnet. Porphyroblasts of amphibole replacing garnet and clinopyroxene characterize stage 4. Retrograde stages 5 and 6 consist of tremolite+Mg-chlorite±serpentine±talc. A high-temperature (∼950°C), spinel-bearing protolith (stage 0), is identified on the basis of orthopyroxene+clinopyroxene+olivine+spinel+amphibole inclusions within stage 1 garnet. The P-T estimates for stage 1 are indicative of UHP conditions (3.2-3.3 GPa and 764-820°C), whereas stage 2 is constrained between 726-788°C and 2.6-2.9 GPa. St